Foreign Direct Investment and Industrial Growth in Algeria: A Nonlinear ARDL Approach - Bakdi Malika, Abdeldjalil Chellig, (European Economic Letters (EEL), 2024)
This paper attempts to find the effect of foreign direct investment on total factor productivity in Algeria’s industrial sector. We use the classical paradigm of Solow and a Cobb-Douglas function, to estimate total factor productivity as a proxy for measuring industrial growth. Moreover, trade openness, and human capital which were the main variables are used as determinants of industrial growth, by applying the non-linear autoregressive distributed lag model method over the period 1990-2019. The main findings indicate the presence of asymmetric relations between foreign direct investment and total factor productivity in the long and the short-run time. Furthermore, the estimation results demonstrate an asymmetric interaction between trade openness and total factor productivity in the long-run, both in the short-run time, indicating that positive and negative changes in trade openness induce a decrease in total factor productivity in the industrial sector. Finally, human capital has a positive impact on total factor productivity in the industrial sector.